FUNCTIONAL ANATOMY OF MANDIBULAR NERVE - Msy Rulan Adnindya; Indri Seta Septadina; Tri Suciati; Wardiansah Wardiansah (Fakultas Kedokteran Universitas Sriwijaya, 2023)
The mandibular nerve is the largest branch of the trigeminal nerve. It innervates the mandibular teeth, gums, skin of the temporal region, ear, lower lip, the lower part of the face, muscles of mastication, and mucous membrane of the anterior 2/3 of the tongue. The mandibular nerve is the main pharyngeal nerve arch. The sensory and motor fibers in the mandibular nerve originate from two roots: the sensory root, which originates from the semilunar ganglion, and the motor root, which originates from the motor nucleus. The mandibular nerve has a mixture of sensory and motor nerves and motor and sensory functions. Face, cheeks and temples, oral cavity, teeth and gums, nasal cavity and sinuses, and temporomandibular joints and muscles. Trauma to the mandible can damage or tear the inferior alveolar nerve in the mandibular canal, causing sensory loss distal to the lesion. Local anesthesia of the inferior alveolar nerve is generally reserved for dental procedures. Local anesthetic injection into the oral mucosa on the medial side of the mandible can also involve the nearby lingual nerve, thus affecting the tongue and the inside of the mouth. The close connection between the submandibular canal and the lingual nerve is important in root canal infections and surgical procedures.